2010
DOI: 10.1073/pnas.0907908107
|View full text |Cite
|
Sign up to set email alerts
|

T7 phage protein Gp2 inhibits the Escherichia coli RNA polymerase by antagonizing stable DNA strand separation near the transcription start site

Abstract: Infection of Escherichia coli by the T7 phage leads to rapid and selective inhibition of the host RNA polymerase (RNAP)-a multisubunit enzyme responsible for gene transcription-by a small (∼7 kDa) phage-encoded protein called Gp2. Gp2 is also a potent inhibitor of E. coli RNAP in vitro. Here we describe the first atomic resolution structure of Gp2, which reveals a distinct run of surfaceexposed negatively charged amino acid residues on one side of the molecule. Our comprehensive mutagenesis data reveal that tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(116 citation statements)
references
References 26 publications
7
109
0
Order By: Relevance
“…S1) intermediates on the pathway to the final R-loop complex. Similar methodology has been applied to study mechanisms of duplex DNA destabilization by RNA polymerases and a variety of enzymes that use base flipping to gain access to bases in the double-stranded DNA (17,18). To determine equilibrium dissociation constant (K d ) values of dCas9/sgRNA complexes with various probes quantitatively, we measured the ability of these probes to affect the rate of dCas9/sgRNA binding to "Cas9 beacons," fluorescently labeled DNA fragments containing the protospacer and PAM, competitively (19).…”
Section: Resultsmentioning
confidence: 99%
“…S1) intermediates on the pathway to the final R-loop complex. Similar methodology has been applied to study mechanisms of duplex DNA destabilization by RNA polymerases and a variety of enzymes that use base flipping to gain access to bases in the double-stranded DNA (17,18). To determine equilibrium dissociation constant (K d ) values of dCas9/sgRNA complexes with various probes quantitatively, we measured the ability of these probes to affect the rate of dCas9/sgRNA binding to "Cas9 beacons," fluorescently labeled DNA fragments containing the protospacer and PAM, competitively (19).…”
Section: Resultsmentioning
confidence: 99%
“…By binding to the β′-jaw inside the RNAP active site channel, Gp2 sterically (Fig. S5) and electrostatically (6,7) interferes with the proper positioning of DNA in the RNAP downstream duplex DNA channel. However, in the absence of σ 70 1:1 , promoter DNA can effectively compete with Gp2, so Gp2 inhibition is compromised (5-7).…”
Section: Resultsmentioning
confidence: 99%
“…S4) (19). The Gp2-β′ R56-E1188 and R58-E1158 interactions are critical for Gp2 binding to, and inhibition of, RNAP (4,6).…”
Section: Significancementioning
confidence: 99%
“…Anti-s factors bind to a s factor and block its interaction with RNAP to prevent complete holoenzyme formation (Campbell et al 2003;Lambert et al 2004;Sorenson et al 2004;Baxter et al 2006). Some anti-s factors also interfere with the interaction between s and DNA by blocking the DNAbinding site of s. The T7 gp2 protein binds and occludes the DNA-binding channel of RNAP (Camara et al 2010;Nechaev and Severinov 2003). In contrast, the present study revealed that the phage protein gp39 functions via a novel, unanticipated mechanism by repositioning the promoter-binding determinant (s 4 ) without interacting with DNA, dissociating the host s factor from RNAP, masking the DNA-binding determinants of s, or occluding the RNAP channels.…”
Section: Discussionmentioning
confidence: 99%